Bridging Conservative and Modern Approaches: Muhammad’s ‘Abduh’s Interpretation of al-Fatihah - Najmah Sayuti; Fadlil Munawwar Manshur (Universitas Islam Negeri Sunan Kalijaga, 2020)
Muḥammad ‘Abduh (1849-1905) is a modern Moslem scholar of Egypt. He was known as a reformist and an architect of Islamic modernism. Through his modernism, he introduced a synthesis of Islamic teachings and modern thought in order to bridge between conservative and modern approaches. This present paper is analysis of his tafsīr on al-Fātiḥah to understand his mix approches. The author found that ‘Abduh’s tafsir applied conservative language to reflect his radical ideas. However, ‘Abduh also introduced modern approaches in his tafsīr. Finally, it is found that al-Fātiḥah in ‘Abduh tafsir contains the substantial messages of the Qur’an.